Assessment of the determinants of pharmacy-based immunization prior to its utilization in Manila - Cortes, Ma. Elaine D.​; Silo, Marie Kyla Louise D.​; Sales, Jaybie A.​ (2017)
Immunizations are crucial to protecting patients from developing and dying from vaccine- preventable diseases (Terrie, 2016). In the Philippines, the administration of adult vaccine is now approved as an additional scope of the pharmacy practice in the recently passed New Pharmacy Law RA 10918 N Section IV. In line with the preventive aspects of pharmaceutical care, the American Society of Health- System Pharmacists (ASHP) has established guidelines on the Pharmacists' Role in Immunization. Pharmacy-based immunization (PBI) would contribute to the effort by providing more accessible and cheaper immunization service. Thus, it is important to identify and evaluate the determinants of PBI prior to its utilization relative to the general public?s view about the immunization program itself and the expanded service of pharmacies in participation to immunization service.